Impact of foreign direct investment on host country’s development: a case study - Tvaronavičienė, Manuela; Šimelytė, Agnė; Burinskienė, Aurelija; Raudeliūnienė, Jurgita; Stirblytė, Gerda (Business, Management and Economics Engineering, 2024)
Purpose is to assess the impact of the inward Nordic foreign direct investment on Lithuania’s exports. Research methodology – this research applied correlation and regression analysis, as well as the Augmented Dickey–Fuller test and the Granger causality test were used. Findings proved that interlinkages between Lithuanian exports and foreign direct investment from the different Nordic countries might vary from weak (Iceland and Denmark) to strong (Norway, Sweden, Finland). Research limitations – greater availability of a statistical dataset covering the classification of foreign direct investment according to the investing country and the distribution of these investments and gross domestic product by economic activity would allow a more accurate assessment of the relationship between Scandinavian foreign direct investment inflows in individual economic sectors and the economic indicators of these sectors. Practical implications – based on the research results, Lithuania has the potential to stimulate exports from inward Nordic foreign direct investment, especially Norwegian foreign direct investment in manufacturing. Originality/Value – this study contributes to the internationalization theory by extending it from the sectorial angle, especially emphasizing the need to analyze the impact of foreign direct investment from a single country on the host economy and its economic structure.